Temperature-dependent 3D structures of lanthanide coordination polymers based on dicarboxylate mixed ligands. Issue 46 (17th October 2018) - Chainok, Kittipong; Ponjan, Nutcha; Theppitak, Chatphorn; Khemthong, Phailyn; Kielar, Filip; Dungkaew, Winya; Zhou, Yan; Batten, Stuart R.
Abstract : Four families of fourteen three-dimensional (3D) lanthanide coordination polymers (CPs) with dicarboxylate mixed ligands have been synthesized hydrothermally at different temperatures. Abstract : Fourteen three-dimensional (3D) lanthanide coordination polymers (CPs) with dicarboxylate mixed ligands, [Ln(fum)1.5 (H2 O)2 ]·0.5(H2 bdc)·H2 O (Ln = Sm (1 ), Tb (2 )), [Ln2 (fum)2 (bdc)(H2 O)4 ]·2H2 O (Ln = Sm (3 ), Eu (4 ), Tb (5 ), Er (6 )), [Ln(fum)0.5 (bdc)] (Ln = Sm (7 ), Eu (8 ), Tb (9 ), Er (10 )), and [Ln2 (bdc)2 (ox)(H2 O)4 ]·0.7H2 O (Ln = Sm (11 ), Gd (12 ), Tb (13 ), Dy (14 )), have been synthesized hydrothermally from the self-assembly of lanthanide(iii ) ions (Ln 3+ ), fumaric acid (H2 fum), and terephthalic acid (H2 bdc) in the presence of potassium hydroxide at different temperatures. The compounds fall into four classes. Compounds1 and2 were isolated from hydrothermal reactions performed at a relatively low temperature of 100 °C and found to crystallize in the triclinic space group P 1̄. The 3D framework is assembled from 2D layers of [Ln(fum)(H2 O)2 ] units pillared by the chelating fum ligands and has 1D rhombic channels templated by H2 bdc and lattice H2 O molecules. The framework presents a binodal (4, 5)-connectedtcs topology with the point symbol (4 4 ·6 2 )(4 4 ·6 6 ). Raising the reaction temperature to 140 °C resulted in the formation of compounds3–6 . These materials crystallize in the monoclinic system with the polar space group P 21 and feature a 3D network constructed from dinuclear {Ln2 (OCO)6 (H2 O)4 } units interlinked by fum and bdc ligands, showing a uninodal 6-connected two-fold interpenetratedpcu topology. The small channels of the framework are occupied by lattice H2 O molecules. Further increase of the reaction temperature to 160 °C gave rise to the formation of compounds7–10, crystallizing in the orthorhombic space group Pbca . The 3D framework is generated from 2D corrugated sheets of [Ln(fum)] 2+ bound by bdc ligands and contains no intercalated H2 O molecules in the lattice. The framework possesses a trinodal (4, 6, 7)-connected net with the point symbol (4 2 ·6 4 )2 (4 6 ·6 8 ·8)(4 12 ·6 9 )2 . Finally, compounds11–14 contained an in situ generated oxalate (ox) ligand formed under hydrothermal conditions conducted at a high reaction temperature of 180 °C. These compounds crystallize in the monoclinic space group P 21 / c and possess a 3D open framework consisting of a dinuclear [Ln2 (ox)(H2 O)4 ] 2+ unit linked by bridging bdc ligands and has small void channels occupied by lattice H2 O molecules. The frameworks were topologically simplified as a binodal (4, 5)-connectedtcj /hc net with a total point symbol of (4 2 ·5 2 ·7 2 )(4 2 ·5 3 ·7 5 ). In the solid state at room temperature, the Tb (2, 5, 9, and13 ) and Eu (4 and8 ) compounds emit green and red light, respectively.